Types and Abundance of Periphyton in The Ceramic Substrate Placed in The Salo River, Salo District, Kampar Regency - Juliana Ivana Siregar; Clemens Sihotang; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Periphyton is a sessile microscopic organism attach on certain substrate. Research aims to determine the type and abundance of periphyton on ceramic substrate has been carried out in April-May 2015 in the Salo River. There are 3 stations (S1, S2 and S3) for placing the ceramic substrate and for taking water samples. Samplings are conducted once/week for a 4 weeks period. The periphyton samples are brushed from the surface of ceramic substrate (8 cm x 3 cm). The number of ceramic sampled in each station is 10, 6 and 3 pieces in S1, S2 and S3 respectively. Results shown that there are 54 types of periphyton present and they are belonged to 5 classes, namely Bacillariophyceae (36 species), Cyanophyceae (8 species), Chlorophyceae (6 species), Dynophyceae (1 spesies), and Xanthophyceae (3 species). The abundance of periphyton in the ceramic substrate placed in the S1, S2 and S3 is significantly different, there were 9,169 cell/cm2 ; 22,002 cell/cm2 and 67,913 cell/cm2 respectively.Keywords : Salo River, periphyton, ceramic substrate, type and abundance